2020
DOI: 10.1128/aac.00824-20
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans as a Model System To Assess Candida glabrata, Candida nivariensis , and Candida bracarensis Virulence and Antifungal Efficacy

Abstract: Although Candida albicans remains the major etiological agent of invasive candidiasis, Candida glabrata and other emerging species of Candida are increasingly isolated. This species is the second most prevalent cause of candidiasis in many regions of the world. However, clinical isolates of Candida nivariensis and Candida bracarensis can be misidentified and are underdiagnosed due to shared phenotypic traits with C. glabrata. Little is known about both cryptic species. Pathogenesis studies are therefore needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 65 publications
5
18
1
Order By: Relevance
“…These results are comparable to those obtained in other studies, which observed that C. auris caused death of G. mellonella within 48 h [ 21 , 22 ] and of C. elegans between 48 and 96 h post-infection [ 23 , 29 ]. Our findings corroborate the idea that both models successfully demonstrate the virulence potential of C. auris , which was similar to or higher than that of other Candida species [ 11 , 30 , 32 , 33 , 52 ]. The observed virulence of C. auris was comparable to C. albicans [ 21 , 22 , 29 ] and higher than isolates from C. haemulonii complex species [ 11 , 29 ].…”
Section: Resultssupporting
confidence: 89%
“…These results are comparable to those obtained in other studies, which observed that C. auris caused death of G. mellonella within 48 h [ 21 , 22 ] and of C. elegans between 48 and 96 h post-infection [ 23 , 29 ]. Our findings corroborate the idea that both models successfully demonstrate the virulence potential of C. auris , which was similar to or higher than that of other Candida species [ 11 , 30 , 32 , 33 , 52 ]. The observed virulence of C. auris was comparable to C. albicans [ 21 , 22 , 29 ] and higher than isolates from C. haemulonii complex species [ 11 , 29 ].…”
Section: Resultssupporting
confidence: 89%
“…Reports indicate that in the same way there are differences in the virulence factors among the C. glabrata complex species, there are also differences in their antifungal resistance. For example, reports show that C. glabrata sensu stricto is more susceptible to fluconazole, itraconazole, and voriconazole than C. nivariensis [ 62 , 63 , 92 ].…”
Section: Antifungal Resistance Of the C Glabrata Complexmentioning
confidence: 99%
“…However, due to the difficulty differentiating them from C. glabrata sensu stricto , the clinical significance and actual prevalence of C. nivariensis and C. bracarensis have been underestimated. The latter affects their treatment, as they exhibit greater resistance to azoles and echinocandins [ 57 , 58 , 61 , 62 , 63 , 64 ]. It should be noted that the increasing use of azole antifungals for the treatment of superficial and systemic infections by Candida glabrata has led to the selection and emergence of resistant isolates, as well as increased infections by other non- albicans species [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo efficacy of known antifungal drugs and a number of repurposed drugs have also been applied in the treatment of nematode candidiasis. Several azoles (Souza et al, 2018;Hernando-Ortiz et al, 2020), echinocandins (Souza et al, 2018), polyenes-particularly amphotericin B (Hernando-Ortiz et al, 2020), and b-lactam antibiotics (in combination with vancomycin) (De Aguiar Cordeiro et al, 2018) have been evaluated for their in vivo efficacy at varying effective concentrations in rescuing worms infected with Candida species (Table 6). Synthesized azole drugs, such as 1-(4cyclopropyl-1H-1,2,3-triazol-1-yl)-2-(2,4-difluorophenyl)-3-(1H-1,2,4-triazol-1-yl) propan-2-ol, have also been evaluated for both efficacy and cytotoxicity in a C. elegans model (Chen et al, 2017).…”
Section: Ahamefule Et Almentioning
confidence: 99%